2016
DOI: 10.1111/gbb.12318
|View full text |Cite
|
Sign up to set email alerts
|

TNF receptors 1 and 2 exert distinct region‐specific effects on striatal and hippocampal grey matter volumes (VBM) in healthy adults

Abstract: Tumour necrosis factor alpha (TNFα) has been implicated in the pathophysiology of neurodegenerative and neuropsychiatric disease, with research highlighting a role for TNFα in hippocampal and striatal regulation. TNFα signals are primarily transduced by TNF receptors 1 and 2 (TNFR1 and TNFR2), encoded by TNFRSF1A and TNFRSF1B, which exert opposing effects on cell survival (TNFR1, neurodegenerative; TNFR2, neuroprotective). We therefore sought to explore the respective roles of TNFR1 and TNFR2 in the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…It was revealed that the changes in both microstructure and function of the brain between men and women were associated with the varied presentation of aggression, impulsivity, and excitement in schizophrenia [ 22 24 ]. It was shown that genetic variants of TNFR1 and TNFR2 are associated with the striatal and hippocampus morphology in healthy people [ 18 ]. It is worth noting that there have been revealed participation of tested SNPs of TNFR2 gene in the modulation of symptoms of the central nervous system which coexist with other diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was revealed that the changes in both microstructure and function of the brain between men and women were associated with the varied presentation of aggression, impulsivity, and excitement in schizophrenia [ 22 24 ]. It was shown that genetic variants of TNFR1 and TNFR2 are associated with the striatal and hippocampus morphology in healthy people [ 18 ]. It is worth noting that there have been revealed participation of tested SNPs of TNFR2 gene in the modulation of symptoms of the central nervous system which coexist with other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the frequency of some alleles in the human TNFR2 gene has been correlated with decreased TNFR2 expression [ 17 ]. The rs1061624 SNP was also associated with a hippocampus volume in healthy adults [ 18 ]. The rs1061622 (T/G) SNP is located in exon 6 at 676 nucleotide of TNFR2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…So far, studies revealing the heterogenous functions of microglia and microglial molecules in different human brain regions have been rare. In an imaging genetics study, respective roles of TNFα receptors, i.e., TNFR1 and TNFR2, in regulation of hippocampal and striatal morphologies in healthy human subjects was explored [87]. TNFα is one of the key microglia-derived cytokines that are known to regulate synaptic transmission and cognition [88].…”
Section: Heterogeneity In Microglial Functions Across Cns Regions: Frmentioning
confidence: 99%
“…TNFR1 and TNFR2 are microglial receptors exerting opposite effects on neuronal survival, with TNFR1 being neurodegenerative and TNFR2 neuroprotective [89]. Interestingly, TNFRSF1A (encoding TNFR1) single nucleotide polymorphisms (SNPs) rs4149576 and rs4149577 were found to have highly significant genotypic associations with striatal but not hippocampal volume, whereas TNFRSF1B (encoding TNFR2) SNP rs1061624 yielded a significant association with hippocampal but not striatal volume [87]. In addition, a most recent transcriptomic study evaluating celltype-specific contribution to cortical thickness in the adolescent human brain showed that inter-regional profiles in cortical thickness were 70% dependent on those in the expression of genes marking CA1 pyramidal cells, astrocytes, and microglia; and these genes were also related to age-dependent cortical thinning [90].…”
Section: Heterogeneity In Microglial Functions Across Cns Regions: Frmentioning
confidence: 99%
“…T1-weighted high resolution anatomical images were acquired (Gyroscan Intera 3T, Philips Medical Systems, Best, NL) with a 3D fast gradient echo sequence ('Turbo Field Echo', TFE), TR= 7.4 ms, TE = 3.4 ms, FA = 9°, two signal averages, inversion prepulse every 814.5 ms, acquired over a field of view of 256(FH) × 204 (AP) × 160(RL) mm, phase encoding in AP and RL direction, reconstructed to cubic voxels of 0.5 × 0.5 × 0.5 mm. The VBM8toolbox (http://dbm.neuro.uni-jena.de/vbm) was used for preprocessing the structural images with default parameters as described before Redlich et al, 2016;Stacey et al, 2016). Briefly, images were bias-corrected, tissue classified, and normalized to MNI-space using linear (12-parameter affine) and nonlinear transformations, within a unified model including high-dimensional DARTEL-normalization and smoothed with a Gaussian kernel of 8 mm full width half maximum (FWHM).…”
Section: Structural Mrimentioning
confidence: 99%